Social Responsibility in the Context of Medical Reform in Ukraine and Georgia (Economics and region, 2018)
The main aspects of the medical reform in Ukraine and Georgia are considered in the article. The main stages of reform in Georgia are determined.
Keywords: social responsibility; health; family physician; medical care; health care reform